Perkembangan Kinerja Keuangan di Kabupaten Trenggalek Dari Tahun 2018-2021 Sebagai Perbandingan Kinerja Sebelum dan Setelah Terjadinya Pandemic Covid-19 di Kabupaten Trenggalek - Eferyn, Krissantina; Riningsih, Duwi; Pramana, Andy Chandra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
The purpose of this study is to determine the development of financial performance in Trenggalek District from 2018-2021 as a comparison of performance before and after the Covid-19 pandemic. This type of research is quantitative descriptive research. The variables used in this study include the Independence Ratio, the Effectiveness and Efficiency Ratio, and the Growth Ratio. The results obtained in this study are that the ratio of financial independence has fluctuated. There was an introduction of independence in 2019 but then it decreased in 2020. In 2019 and 2020 there was a decrease in effectiveness and it rose again in 2021 but the financial performance of Trenggalek district in 2018-2020 was included in the effective and very effective category. For efficiency ratios, the best occurred in 2019. The Covid pandemic caused a decrease in efficiency ratio performance. Performance has again experienced an improvement in the efficiency ratio in 2021.